2023
DOI: 10.1002/alz.13400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise engagement and cardiovascular risk on neuronal injury

Abstract: INTRODUCTIONNeuronal health as a potential underlying mechanism of the beneficial effects of exercise has been understudied in humans. Furthermore, there has been limited consideration of potential moderators (e.g., cardiovascular health) on the effects of exercise.METHODSClinically normal middle‐aged and older adults completed a validated questionnaire about exercise engagement over a 10‐year period (n = 75; age 63 ± 8 years). A composite estimate of neuronal injury was formulated that included cerebrospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…In fact, improved cognition was also observed over a 4-year period for those more engaged in physical activity. Interestingly, in a different study of middle-aged and older adults, Stojanovic et al [15] found greater physical activity engagement was associated with less plasma NfL in a group with low cardiovascular risk (i.e., The Framingham Risk Score), but not in a group with higher cardiovascular risk. This suggests that the benefits of physical activity are attenuated by cardiovascular risk.…”
mentioning
confidence: 97%
“…In fact, improved cognition was also observed over a 4-year period for those more engaged in physical activity. Interestingly, in a different study of middle-aged and older adults, Stojanovic et al [15] found greater physical activity engagement was associated with less plasma NfL in a group with low cardiovascular risk (i.e., The Framingham Risk Score), but not in a group with higher cardiovascular risk. This suggests that the benefits of physical activity are attenuated by cardiovascular risk.…”
mentioning
confidence: 97%